2010
DOI: 10.1002/ajmg.a.33580
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a submicroscopic 3.2 Mb chromosomal 16q12.2‐13 deletion in a child with short stature, mild developmental delay, and craniofacial anomalies, by high‐density oligonucleotide array‐a recognizable syndrome

Abstract: Interstitial deletion of 16q has emerged into a recognizable pattern of congenital malformation. We report on a 9-year-old boy with short stature, psychomotor retardation, high forehead, broad flat nasal bridge, hypertelorism, cup-shaped ears, short neck, and a normal karyotype. Using high-density oligonucleotide array chip (Affymetrix 6.0) to perform parental and proband samples concurrently on three chips and interpreted as a trio set, a de novo 3.2 Mb deletion from bands q12.2 to q13 on chromosome 16 (from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…Interstitial deletions of the 16q centromeric region are rare and only a small number of patients have been reported (Ballif et al . ; Borgatti et al ; Chang et al ). In this study, we identified a patient with a rare interstitial 16q12.2q21 microdeletion and studied the genotype‐phenotype correlation in comparison with previously reported patients.…”
Section: Introducationmentioning
confidence: 99%
“…Interstitial deletions of the 16q centromeric region are rare and only a small number of patients have been reported (Ballif et al . ; Borgatti et al ; Chang et al ). In this study, we identified a patient with a rare interstitial 16q12.2q21 microdeletion and studied the genotype‐phenotype correlation in comparison with previously reported patients.…”
Section: Introducationmentioning
confidence: 99%
“…Deletion on 16q12 region has been extensively studied in decades in relation to syndromic cases with various phenotypes and one of the craniofacial anomalies identified was high‐arched palate or cleft of the soft palate (Callen et al, ; Chang et al, ; Elder, Ferguson, & Lockhart, ; Shoukier et al, ). Therefore, there is high possibility that this mutation also occurred in nonsyndromic cleft cases but the specific mechanism of action of TOX3 confers craniofacial deformity risk was unclear.…”
Section: Discussionmentioning
confidence: 99%
“… Schematic representation of the 16q12.1q12.2 deletion in our patient and previously published reports of patients with overlapping deletions. The bi‐directional arrow indicates the SROs and OMIM genes (bottom) in Patients 1, 2 [Ballif et al, 2008], 3 [Bardakjian et al, 2009], 4 [Borozdin et al, 2006], 5 [Matthaei et al, 2005], and a partially overlapping deletion in 16q12.2‐q13 that was published recently by Chang et al [2010] (patient 6). The clinical details are summarized in Table I.…”
Section: Discussionmentioning
confidence: 99%
“…Haploinsufficiency of the ZNF423 gene has also been postulated as the underlying cause of intellectual disability and other features associated with microdeletions of 16q11.2q12.2 [Ballif et al, 2008]. In addition, Chang et al [2010] recently published a 3.2‐Mb deletion in bands 16q12.2 to q13 in a child with short stature, mild developmental delay, and craniofacial anomalies.…”
Section: Introductionmentioning
confidence: 99%